Chemical composition, antimicrobial, and antioxidant activities of orange essential oil and its concentrated oils - Torres Álvarez, Cynthia; Núñez González, A.; Rodríguez, J.; Castillo, S.; Leos Rivas, Catalina; Báez González, Juan Gabriel (Taylor & Francis, 2016)
In this study, the chemical composition, antimicrobial, and antioxidant activities of orange essential oil (AN), its folded orange oils (5×, 10×, 20×) and d-limonene (LN) were investigated. The results observed in the chemical composition showed a decrease in the major component LN, in contrast to other minor components, which increased their concentration, such as decanal, linalool, and α-terpineol. The antimicrobial activity was determined for foodborne pathogens using the disk diffusion method followed by the minimum inhibitory concentration and minimum bactericidal concentration. Results showed that folded orange oils (5×, 10×, 20×) had better antimicrobial activity than AN and LN. The antioxidant activity was carried out by 2,2ʹ-azinobis-3-ethylbenzthiazoline-6-sulphonate and 1,1-diphenyl-2-picrylhydrazyl methods; folded orange oil 20× presented significantly better results (p ≤ 0.05) than other oils studied. Using folded oils from AN could be a natural alternative in food processing as ingredients with antimicrobial and antioxidant effect.